Speaker Gender Representation for Anesthesiology Grand Rounds at a Large Academic Medical Center - Kraus, Molly B. (J Educ Perioper Med, 2020)
BACKGROUND: Invited speakerships, such as speaking at grand rounds, are part of the pathway to promotion in academic medicine. This project sought to evaluate if the gender of invited grand rounds speakers at a major academic institution were distributed as expected based on the specialty workforce. MATERIALS AND METHODS: Archived lists of speakers for grand rounds for the Mayo Clinic Department of Anesthesiology were obtained from 2007 through 2018. The Cochran-Armitage test and logistic regression models were used to analyze the change in proportion of invited women speakers over time. One-sample proportion tests were conducted to compare the proportion of women speakers to the expected percentage of available women speakers based on gender data from national organizations. RESULTS: Of the 122 invited external speakers, 28 (23%) were women. Men invited 104/122 (85.2%) of all the speakers, of which 21 (20.2%) were women speakers. There was not significant evidence the proportion of women speakers increased over time (P = .29). Women speakers comprised a lower proportion of external invited speakers compared to the proportion of women in the academic anesthesia workforce; however, this association was not statistically significant (P = .07). The percentage of new residents that were female increased over this time period (P = .001). DISCUSSION: The percentage of women invited to be grand rounds speakers did not increase over the study period. Intentional measures should be instituted to increase the proportion of women grand rounds speakers.